The Influence of Audit Complexity, Time Budget Pressure, and Auditor Competence on Audit Quality at The Inspectorate General of The Audit Board of The Republic of Indonesia - Sastha, Arga; Sudirgo, Tony (Green Publisher Indonesia, 2025)
This study aims to analyze the influence of audit complexity, time budget pressure, and auditor competence on audit quality at the Inspectorate General of the Audit Board of the Republic of Indonesia (BPK RI). The research employs a quantitative approach using a survey method involving 96 internal auditors at the Inspectorate General of BPK RI, with data analyzed through multiple linear regression using statistical software. The results indicate that audit complexity has a significant negative effect on audit quality, auditor competence has a significant positive effect, while time budget pressure has no significant effect. These findings suggest that audit quality can be improved by strengthening auditor competence and managing the complexity of audit tasks, even though time pressure is not a directly determining factor in audit implementation. These results are expected to provide useful strategic input for BPK RI in improving internal audit quality and serve as a practical reference for auditors and other supervisory institutions in managing the various factors that influence the overall quality of audit outcomes